La crítica anticartesiana de Michel Foucault al psicoanálisis en Historia de la locura - Marco Alexis Salcedo (Theoría Revista del Colegio de Filosofía, 2013)
The following text corresponds to an analysis of the main arguments presented by Michel Foucault in History of Madness against the psychoanalytic doctrine. It is argued that the father of the psychoanalysis is challenged because of his affiliation to Cartesian thought that Foucault identified in his doctrine. The text points out that for Foucault, this filiation renders inoperative for psychoanalysis to understand the Unreason, and its device becomes a contemporary version of the clinical structures put into practice in the asylum of the nineteenth century. It concludes stating that Foucault’s philosophical stance against Descartes is probably based on the distinction he made in favor of the philosophical project of modernity that Kant established with his thought.